2016
DOI: 10.1097/bot.0000000000000499
|View full text |Cite
|
Sign up to set email alerts
|

Suprapatellar Versus Infrapatellar Tibial Nail Insertion

Abstract: Therapeutic Level II. See Instructions for Authors for a complete description of levels of evidence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
132
3
4

Year Published

2017
2017
2020
2020

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 116 publications
(146 citation statements)
references
References 17 publications
7
132
3
4
Order By: Relevance
“…However, the previous studies showed different results compared to our studies [13,14] [22]. Moreover, Aksahin et al [26] found that the damage to quadriceps might worsen the patellar tilt due to the sagittal patellar tilt and quadriceps hypotrophy after tibial nailing, besides, the displacement of patella might have a negative impact on the knee function.…”
Section: Resultscontrasting
confidence: 74%
See 1 more Smart Citation
“…However, the previous studies showed different results compared to our studies [13,14] [22]. Moreover, Aksahin et al [26] found that the damage to quadriceps might worsen the patellar tilt due to the sagittal patellar tilt and quadriceps hypotrophy after tibial nailing, besides, the displacement of patella might have a negative impact on the knee function.…”
Section: Resultscontrasting
confidence: 74%
“…However, for the HSS component, our study showed that the IP approach was superior to SP approach with respect to the range of motion.Evaluation of the overall HSS knee score of SP and IP approaches for the treatment of tibial shaft fracture in this study demonstrated comparable outcomes. Our results are in line with the previous data reporting comparable functional knee outcomes between SP and IP approaches[14,15]. Chan DS et al compare the clinical outcomes of the knee joint after SP versus IP tibial nail insertion in a prospective randomized study with 42 patients and 12 months of follow-up, and reported no…”
supporting
confidence: 92%
“…Daniel S. Chan et al conducted a prospective randomised pilot study to compare the clinical and functional outcomes of the knee joint after infrapatellar versus suprapatellar tibial nail insertion. [7] The results were that a total of 41 patients/fractures were enrolled in this study. Of those, only 25 patients/fractures (14 IP, 11 SP) fully complied with and completed 12 months of follow-up.…”
Section: Discussionmentioning
confidence: 95%
“…It also avoids elevated compartment pressures seen with prolonged traction. [6][7][8][9][10] Anterior knee pain is one of the most common complaints after tibial intramedullary nailing. This has a significant economic impact, since the majority of tibial fractures that require nailing are sustained by men with an average age of 31 years.…”
Section: Name and Address Of Corresponding Authormentioning
confidence: 99%
“…There is increasing interest in the literature in the use of the suprapatellar approach rather than the traditional infrapatellar approach as this may reduce this complication. Although to our knowledge, no randomised controlled trial has been published, other studies comparing these approaches have used subjective patient-reported outcome measures (PROMs) rather than objective outcome measures [4,5].…”
Section: Introductionmentioning
confidence: 99%